2020
DOI: 10.1055/s-0040-1718549
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Real-Time Visualization of the Lymphatic Vessels Using Microscope-Integrated Laser Tomography

Abstract: Background Detection and selection of the lymphatic vessels are important for maximizing therapeutic efficacy of lymphaticovenular anastomosis (LVA). Some imaging modalities have been reported to be useful for intraoperative identification of the lymphatic vessels, but they have limitations. In this article, we present new capabilities of intraoperative laser tomography, which was used to evaluate the lumen of the lymphatic vessel and to validate the patency of anastomosis. Patients and Methods Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…However, recent studies revealed that microscope-integrated laser tomography is superior to US in terms of intraoperative evaluation. 39 One of our limitations is that lower extremity lymphedema is overrepresented with 48 cases and 184 dissected lymphatic vessels, probably because patients with lower extremity lymphedema suffer more because of gravity. LVA operations were performed on upper extremity lymphedema patients in 13 cases, where 49 lymphatic vessels were anastomosed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, recent studies revealed that microscope-integrated laser tomography is superior to US in terms of intraoperative evaluation. 39 One of our limitations is that lower extremity lymphedema is overrepresented with 48 cases and 184 dissected lymphatic vessels, probably because patients with lower extremity lymphedema suffer more because of gravity. LVA operations were performed on upper extremity lymphedema patients in 13 cases, where 49 lymphatic vessels were anastomosed.…”
Section: Discussionmentioning
confidence: 98%
“…Another limitation is that US findings depend on the examiner's experience and the examination time. 39 To overcome this limitation, we standardized the examination time to 60 minutes and searched for lymphatic vessels primarily in the fluid-predominant region. This work was performed by the author S.M.…”
Section: Discussionmentioning
confidence: 99%
“…The anastomosis of such sclerotic lymphatic vessels leads to minimal or no therapeutic effect and therefore the identification of overloaded yet functional lymphatics has crucial importance in LVA surgery. 10 11 12…”
mentioning
confidence: 99%
“…The anastomosis of such sclerotic lymphatic vessels leads to minimal or no therapeutic effect and therefore the identification of overloaded yet functional lymphatics has crucial importance in LVA surgery. [10][11][12] However, lymphatics represent only one side of LVA, and the recipient venule (RV) selected influences the efficacy of the anastomosis and the surgical outcome likewise the lymphatic side. 9 Despite that, RV for LVA have been usually neglected in literature.…”
mentioning
confidence: 99%
“…For microscopic navigation, a built-in ICG camera system shows the lymphatic vessels and their flow. Moreover, a recent ICG videolymphography system 4 and microscope-integrated laser tomography 5 have the potential to make LVA surgery more accurate and certain. However, for macroscopic ICG navigation, which is performed to detect the best position to make the skin incision and LVA for the whole area of an extremity, we still required a conventional ICG camera system (PDE-neo; Hamamatsu Photonics Co., Ltd, Shizuoka, Japan) displayed on monitors, which means that surgeons must shift their vision between the surgical field and the monitor.…”
mentioning
confidence: 99%